Reading Issues of Race and Ethnicity Through Yellowface Novel as Popular Literature - Azzahra, Rahmasari Putri (Universitas PGRI Adi Buana Surabaya, 2025)
The novel Yellowface by Rf. Kuang has become one of the most popular novels and a best seller since its initial publication. This popularity brings pros and cons by readers because the issue narrated in the novel is an issue that will never be resolved, namely the issue of race and ethnicity in America. This research will use the Goodreads platform to collect data on readers' responses to Yellowface by Rf. Kuang. To analyze this, the researcher uses Stuart Hall's reception theory. The data in this study is taken with a qualitative descriptive method, which describes based on reader reviews on the Goodreads platform. With the theories and methods used, this research will produce data on readers of the novel Yellowface on the Goodreads platform, analyze readers with dominant receptions, analyze readers with negotiated receptions, and analyze readers with oppositional receptions.